(untitled) (International Journal of Engineering and Computer Science, 2014)
Data transmission needs security. Data hiding can be achieved through many methods. Different data hiding techniques are discussed in this paper which includes watermarking, steganography, fingerprinting, cryptography and digital signature. Since internet provides images, audio and video in digital form, distributing copies of copyright material are avoided by adding data hiding methods.